The war on drugs and Anglo-American relations : lessons from Afghanistan. - BERRY, PHILIP (EDINBURGH UNIV Press, 2018)
Reveals the inside story of the formulation and implementation of the US and UK's counter-narcotics policies in Afghanistan Through interviews with key policy practitioners on both sides of the Atlantic, this study reveals the complex picture of counter narcotics strategy in Afghanistan. It highlights the key points of cooperation and contention, and details the often contradictory and competitive objectives of the overall war effort in Afghanistan. Western counter-narcotics policies in Afghanistan failed dismally after opium poppy cultivation surged to unprecedented levels. The Anglo-American partnership at the centre of this battleground was divided by competing and opposing views of how to address the opium problem, which troubled the well-established Anglo-American relationship.
Keywords: Drug control -- Afghanistan -- International cooperation.; Opium trade -- Afghanistan.; Lutte antidrogue -- Afghānistān -- Coopération internationale.; Opium -- Commerce -- Afghānistān.; Drug control -- International cooperation; Opium trade; Afghanistan